Estimation of Shelf Life â€œHalua Kenariâ€ using Accelerated Shelf Life Testing (ASLT) Method Arrhenius Model at Small And Medium Enterprises at Sitaro Archipelago - Pongajow, Novke J.; Djarkasi, Gregoria S. S.; Mandey, Lucia C. (Pascasarjana Unsrat, 2015)
The halua kenari is one of the signature product from North Sulawesi especially Minahasa and Siau. Fat and oil oxidation processes lead to taste and flavor dislike and degradation of nutrition and functional characteristics. Beside chemical composition, halua kenari degradation accelerated by improper handling and packing during transportation, distribution, and storage by consumer and seller. The aims of this research is to predict shelf life of halua kenari production ofÂ Small And Medium Enterprises at District of Sitaro Archipelago with accelerated shelf life testing model (Arrhenius) and to get shelf life model of halua kenari production at small and medium enterprises at Sitaro Archipelago. This research was done in two stages which is determination of quality characteristic of halua kenari by chemical analysis and organoleptic test and shelf life of halua kenari by Accerelated Shelf Life Testing (ASLT) Model. Product was stored at extreme temperature to fasten deterioration. Data extrapolated to mathematical model Arrhenius. The processing characteristic, temperature, andÂ storage are very significant to quality degradation and shelf life of halua kenari. The shelf Â life of halua kenari product with low fat and oil (A1) that stored at 30 o C is 106 days, as halua kenari with high fat and oil stored in the same temperature and days, found : A2 with 18 days shelf life, A3 with 23 days shelf life, and A4 with 17 days shelf life. Keywords : the halua kenari, the shelf life, Arrhenius model, water content, and FFA